Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Etos Kerja Guru PAI di Sekolah - Agung Agung; Muhammad Aditya Firdaus; Umar Rosadi (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study focuses on the declining work ethic of PAI teachers, indicated by the performance of teachers in improving teaching and learning activities that is still low, less concerned about duties and responsibilities, weak dedication and loyalty in carrying out tasks and weak responsiveness when curriculum changes occur. The research approach used is a qualitative approach with a descriptive method. Data collection techniques using interview observations and documentation studies. The results of this study are 1) the principal acts as an Educator; manager; administrator; supervisors; leaders; innovator; motivator. 2) There are at least three strategies used, namely hierarchical strategies, transformational strategies, and facilitative strategies. In realizing this strategy, the principal equalizes the rights and obligations of each teacher, provides information according to the needs of each teacher and according to their capacity, provides discussion space for teachers to solve each problem.